Peran Guru dan Orang Tua dalam Pembelajaran Daring di Sekolah Dasar - Endang Sri Maruti; Hanuwati Anurilandhan Hidayat; Daffa Adhiza Ilfani (Madako Elementary School, 2023)
The focus of this research are 1) The teacher's role in online learning during the Covid 19 pandemic, 2) The role of parents in online learning during the Covid 19 pandemic. 3) The impact and difficulties encountered in online learning during the Covid 19 pandemic. This research uses qualitative research case study research. The subjects in this study were students, teachers and parents of fifth grade students at SDN Jatisari 2 Madiun Regency. Collecting data using observation, interviews and documentation as well as data analysis and drawing conclusions in this study using triangulation. The results show that during online learning parents actually try to accompany their children to study online at home. However, the busyness of parents sometimes makes children unable to be directly guided by their parents because of the limited time and competence of parents. The teacher's role in online learning is to monitor student progress, deliver material and assignments via WhatsApp groups and ask about difficulties experienced by students and explain. The impact experienced by students is that students feel bored and bored with this online learning system so that there is a need for creativity and innovation from teachers in delivering learning material.